Effects of Snow and Dust on Radiation and Temperature in Qinghai Lake during Ice-covered Period - Ruijia NIU; Lijuan WEN; Mengxiao WANG; Yixin ZHAO; Jingwei DONG; Guantian WANG; Qi WANG (Gaoyuan qixiang)
Many lakes are widely and densely distributed on the Qinghai-Tibet Plateau.Due to the high altitude， the lakes seasonally freeze with a long ice-covered period.Lake ice can significantly affect the local and regional climate and the sub-glacial aquatic ecosystem by changing the transfer process of radiation energy on and in the lakes.However， their characteristics during the ice-covered period still remain unclear.Therefore， from February 6 to 28， 2022， we conducted a systematic observation of water ice air in Qinghai Lake， the largest lake on the Qinghai-Tibet Plateau.Using field observation data， video images and the precipitation data of peripheral observation stations， the influence of different ice cover conditions on the radiation and temperature of the water-ice-atmosphere on Qinghai Lake during the ice-covered period was analyzed.Results showed that different weather processes such as snowfall， sand and gale could remarkably change the property of cover on the ice， leading to variations of ice thickness on Qinghai Lake.Furthermore， the discrepancies of solar radiation absorption and reflection of different covers result in energy equilibrium that directly dictate ice surface temperature at water-ice-atmosphere interface.Bare ice with low albedo and low absorption induced the relatively strong net solar radiation and the correspondingly large diurnal variations of ice temperature.Compared to bare ice， the high reflection of snow cover and the strong absorption of sand and dust make the ability of net short-wave radiation to penetrate ice weaker， and the diurnal variation of lake ice temperature is smaller.